Clinical experience with ursodeoxycholic acid (Urdoxa) in complex therapy of chronic viral hepatitis - E. V. Esaulenko; O. E. Nikitina; N. V. Dunaeva; A. N. Uskov; T. L. Mogilevets (Журнал инфектологии)
Patients with chronic virus hepatitis (32 patients, 13 with chronic hepatitis B and 19 with chronic hepatitis C) ages from 20 to 72 with elevated levels of bilirubin and active alanine aminotransferase, aspartate aminotransferase, gamma- glutamyl transpeptidase, received ursodeoxycholic acid (Urdoxa) over the course of 12 weeks. During therapy alanine aminotransferase, aspartate aminotransferase, bilirubin and gamma-glutamyl transpeptidase levels decreased. Urdoxa demonstrated good tolerance, efficacy and no visible side effects. Thus, Urdoxa could be used in treatment of chronic viral hepatitis with cytolytic and cholestatic syndromes.